Visceral Leishmaniasis hospitalizations and seasonality in Fortaleza, Ceará, Northeast Brazil between 2003 – 2012 - Leite, Robério Dias; Meneses, Renata Leal; de Magalhães, Thais Fontes; Ogawa, Maurício Yukio; Falcão, Hayssa de Oliveira; Sousa, Anastácio de Queiroz (Journal of Health & Biological Sciences, 2018)
Introduction: The knowledge of the relationship between Visceral Leishmaniosis and climatic aspects is already well established in the literature of other countries, but lack data of this relationship in Brazil. Objective: This study aimed to describe the seasonal distribution of hospitalizations for Visceral Leishmaniosis (VL) in a referral hospital for infectious diseases located in an endemic area of the semiarid in the Northeast of Brazil. Methods: The number of monthly hospitalizations between 2003 and 2012 was recorded retrospectively and was correlated with climate variables. Results: During this period 1,302 patients were hospitalized. We observed an inverse relationship with the monthly amount of precipitation (r = - 0.725; p = 0.008), the number of days per month with precipitation (r = - 0.683; p = 0.0144) and relative humidity (r = - 0.746; p = 0.005) when compared with the monthly number of hospitalizations due to VL. Inversely, there was a direct relationship with the maximum monthly mean temperature and the number of hospitalizations due to VL (r = 0.643; p = 0.024). Conclusions: The rainy season, characterized by more rainfall and higher humidity, was correlated with fewer hospitalizations for VL. Conversely, in months with higher temperatures the number of hospitalizations for VL was higher.